Institutional trades and intraday stock price behavior - Chan, Louis K.C.; Lakonishok, Josef (Journal of Financial Economics, 1993)
This paper examines the price effect of institutional stock trading, using a unique data set that reports the transactions (large and small) of 37 large institutional money management firms. The direction of each trade and the identity of the management firm behind each trade are known. Although institutional trades are associated with some price pressure, we find that the average effect is small. There is also a marked asymmetry between the price impact of buys versus sells. We relate our findings to various hypotheses on the elasticity of demand for stocks, the cost of executing transactions, and the determinants of market impact. Although market capitalization and relative trade size influence the market impact of a trade, the dominant influence is the identity of the money manager behind the trade.